Everything in everything Anaxagoras's metaphysics - Marmodoro, Anna 1975- (Oxford University Press, 2017)
Anaxagoras of Clazomenae (5th century BCE) is best known in the history of philosophy for his stance that there is a share of everything in everything. He puts forward this theory of extreme mixture as a solution to the problem of change he and his contemporaries inherited from Parmenides - that what is cannot come from what is not (and vice versa). Yet, for ancient and modern scholars alike, the metaphysical significance of Anaxagoras's position has proven challenging to understanding. In 'Everything in Everything', Anna Marmodoro offers a fresh interpretation of Anaxagoras's theory of mixture, arguing for its soundness and also relevance to contemporary debates in metaphysics